The Art of Counterpoint: Part Three of Le Istitutioni harmoniche, 1558 - Zarlino, Gioseffo 1517-1590; Marco, Guy A.; Palisca, Claude V. 1921-2001 (New York The Norton Library, 1976)
Zarlino's Le Istitutioni harmoniche, published in 1558, is one of the most influential music treatises of all time. To his contemporaries it revealed the secrets of composition he had learned from Adrian Willaert, who brought to Italy the polyphonic art of the Netherlands. To the modern scholar Zarlino's treatise illumines the compositional technique of the golden age of vocal polyphony. The essence of this art is contained in Part III, "The Art of Counterpoint," which is here translated into English for the first time.
Keywords: Music theory